Recent advances in the therapeutic potential phytochemicals in managing diabetes - Muhammad Mubarak Dahiru (Golestan University Of Medical Sciences, 2023)
Diabetes and diabetic complications have been a global menace for a long time, putting a heavy burden on an individual, the health sector, and governments. Diabetic complications attributed to persistent hyperglycemia create a challenge in managing diabetes, considering the nature of the disease as a group of metabolic disorders. Various phytochemicals target different metabolic pathways and molecules through different mechanisms of action, acting individually or synergistically to achieve therapeutic goals. Phytochemicals such as alkaloids, saponins, glycosides, terpenoids, and flavonoids were reported to exert different anti-diabetic effects, including anti-hyperglycemic, anti-hyperlipidemic, anti-inflammatory, antioxidant, and insulinotropic activities. The present review focused on the recent advances in the therapeutic potentials of phytochemicals in managing diabetes and diabetic complications, emphasizing their in vitro and in vivo studies.